National and foreign lyrical theater in Ecuador until the first half of the twentieth century (Revista Argentina de Musicología, 2020)
This article explores the artistic activities that foreign opera, operetta and zarzuela companies developed in Guayaquil and Quito in the second half of the 19th– and first half of the 20th centuries. It also examines the influence that foreign musicians exerted in the formation of the first national lyrical groups. To this end, I examine the role of theaters, conservatories, artistic societies, businessmen, and students of singing and declamation in the first lyrical productions, both in Quito (1926-1932) and in Guayaquil (1932-1947). The lyrical seasons that foreign companies presented in Ecuador not only popularized the famous European operas, operettas and zarzuelas of the 19th century, but also promoted in the artistic community the desire to make local productions of them. Likewise, this activity promoted in Ecuadorian composers the desire to cultivate similar compositions with themes and scenarios of the country, a repertoire that is currently unknown due to the lack of preservation of the scores.
Keywords: Ecuador; Lyrical Companies; Opera; Angelo Negri